Bangladesh : The Path to Middle-Income Status from an Urban Perspective - Muzzini, Elisa (Washington, DC: World Bank, 2013)
Bangladesh seeks to attain middle-income status by 2021, the 50th anniversary of its independence. To accelerate growth enough to do so, it will need to undergo a structural transformation that will change the geography of economic production and urbanization. Critical to its transformation will be the creation of a globally competitive urban space, defined here as a space that has the capacity to innovate, is well connected internally and to external markets, and is livable (Organization for Economic Cooperation and Development, or OECD 2006; World Bank 2010). This study identifies what is unique about Bangladesh s process of urbanization and examines the implications for economic growth. Through the lens of Bangladesh s most successful industry, the garment sector, it describes the drivers of and constraints to urban competitiveness. Based on the findings, it provides policy directions to strengthen the competitiveness of Bangladesh s urban space in ways that will allow Bangladesh to reach middle-income status by 2021.